Community interest in developing tourist villages based on neuroscience methods - Imam Indratno; Chusarini Chamid; Tonny Judiantono; Vermanda Maharani Sonya; Nurrhisma Yuniar (Universitas Gadjah Mada, 2023)
Rawabogo Village is one of the tourist villages in Bandung Regency with insignificant development since its establishment. Community participation is important in the stages of development. However, measuring context in real time and accurately is generally difficult. Neuroscience can be used to control the validity and subjectivity of the questionnaire and interview methods used to examine neural responses to tourism conditions. Thus this study aims to identify the people of Rawabogo Village's interest in developing a tourism village based on neuroscience methods. The results of the data analysis show that the people of Rawabogo Village have a strong interest in developing a tourist village. The result is indicated by the entropy value obtained and the results of the questionnaire scoring. The neuroscience method in tourism village development acts as a method that supports, complements, and validates existing tourism village development concepts or methods such as Community Based Tourism (CBT).